Prevención, diagnóstico y etiología del bruxismo en odontopediatría. Revisión bibliográfica - Naranjo Brito, Mateo José (2024)
Bruxism is a phenomenon involving the clenching or grinding of teeth, both during sleep and while awake. Its definition has evolved from being simply regarded as teeth grinding during sleep to being understood as a complex motor activity that may indicate the presence of underlying conditions, besides having potential relevance from a physiological or protective perspective. The present study determined different treatment alternatives for bruxism in the pediatric population, the various signs and symptoms presented, and the etiological factors that may cause bruxism in children. This analysis was conducted through a literature review that included the collection, description, and analysis of scientific articles in English and Spanish, published between 2013 and 2023. The documents were selected from various databases, such as Medline/PubMed, Google Scholar, Scielo, and Elsevier. The collected data were structured into tables for further analysis. The results indicated that, regarding treatment alternatives, 100% of the articles considered cognitive-behavioral therapy indispensable for managing this type of patients, followed by pharmacological treatment at 90%, the use of splints and orthodontics at 80%, muscle relaxation at 60%, and surgical approach at 30% less frequently. To determine clinical signs and symptoms, dental wear along with TMJ pain was reported in 100% of cases, followed by headache/myofascial pain and hypertonicity of masticatory muscles at 90%, sleep disorders at 70%, lip/tongue indentations at 60%, and gingival recession with xerostomia presence at 40%. Among the results to determine the etiological factors of bruxism in children, several authors specified that psychological factors had a higher prevalence at 100%, followed by local, systemic, and pathophysiological factors at 90%, hereditary and socioeconomic factors at 70%, pharmacological factor mentioned in 50% of the reviewed articles, and hereditary factor reported in 30%. Conclusively, cognitivebehavioral therapy was utilized by all authors, while coronal restorations were less common. Regarding the clinical aspect of bruxism, dental wear was commonly identified by all authors, while symptoms such as sleep disorders, lip/tongue indentations, and gingival recession showed variability in their presence. Finally, in terms of bruxism etiology, psychological factors were consistently considered by all authors as contributing elements